THE EXISTENCE OF KEDONGANAN AS A CULINARY TOURISM DESTINATION AND LOCAL SOCIO-ECONOMIC DYNAMICS - Liestiandre, SST.Par., M.M., Dr. Hanugerah Kristiono; Yogantari, I Gusti Ayu Istri Agung; Maharani, Ida Ayu Putu Dian; Yuliani, Mega; Tanjung, Gede Febrian Govinda; Pratama, Adhi Nanda Bintang (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2025)
This study aims to analyze the existence of Kedonganan as a culinary tourism destination based on Community-Based Tourism (CBT) and the accompanying socio-economic dynamics amidst increasingly complex business competition. Using a mixed methods approach, data was collected through a survey of 24 culinary business actors, field observations, and in-depth interviews with the Head of BPKP2K. The findings indicate that the implementation of CBT in Kedonganan has successfully encouraged community participation in the tourism sector and increased local income. However, on the other hand, weak regulations that are no longer relevant to developments in the field have triggered unhealthy competition in tariffs and commissions among business actors, as well as fraudulent practices that have damaged the destination's reputation. From an Institutional Theory perspective, the crisis is identified as a crisis of regulatory legitimacy and social disintegration that directly impacts tourism sustainability and tourist satisfaction. Although social norms and community values remain strong, they are not enough to offset the weak oversight system and ineffective sanctions. In response to the crisis, an evidence-based approach has been implemented, accompanied by incentives, training, and cross-stakeholder collaboration to rebuild the collective reputation. This research emphasizes the importance of regulatory reform, fair incentive mechanisms, and strengthening community capacity in maintaining a balance between economic growth, cultural preservation, and social sustainability in community-based tourism destinations.